Išvydę Vydūną - Kardelis, Naglis (Colloquia, 2020)
Vaclovas Bagdonavičius, Aušra Martišiūtė-Linartienė, Vydūnas, Vilnius: Mokslo ir enciklopedijų leidybos centras, 2017, 727 p. ISBN 978-5-420-01796-8.